Fear of the Unknown: Does Fear of Terrorism Differ From Fear of Contracting COVID-19? - Shechory Bitton, Mally; Laufer, Avital (Frontiers in Psychology, 2021)
The aim of the study was to explore whether living under constant security threat would result in better coping and higher resilience when exposed to an unknown threat such as the COVID-19 pandemic. Thus, fear of COVID-19 and fear of terrorism as well as the associations with coping strategies and resilience were examined among Israelis living in conflict zones as well as Israelis living in the center, where exposure to security incidents is rare. Six hundred and fifteen Israeli adults (260 men and 356 women) were interviewed via the internet while Israel was under mandatory first lockdown. Fear of COVID-19 was found to be higher than fear of terrorism among both groups. those living in the conflict zones and those living in the central Israel. In contradiction to our assumption, we found that those who were living in a conflict zone did not exhibit higher levels of resilience and did not cope better when exposed to a new threat—even though they may be more skilled at handling prolonged exposure to a threat such as terrorism. A regression analysis indicated that the best predictor of both fear of COVID-19 and of terrorism is financial concerns—more than geographical area.